A general approach to joint pain focusing on acute monoarthritis - Tedeschi, Sara K. (Henry Stewart Talks, 2018)
Comparison of arthralgia and arthritis, NO PADS acronym for diagnosis, Disease distribution, Acute monoarthritis differential diagnosis, A practical treatment process, Gout management, Common uric-acid lowering medications